Antibiogram of Urinary Tract Infections and Sepsis among Infants in Neonatal Intensive Care Unit - Abdulrahman S. Bazaid; Abdu Aldarhami; Hattan Gattan; Heba Barnawi; Husam Qanash; Ghaida Alsaif; Bandar Alharbi; Abdulaziz Alrashidi; Essam Hassan Eldrehmy (Children, 2022)
Neonatal infections including sepsis and urinary tract infections are considered among the leading causes of mortality in neonatal intensive care units (NICU). Thus, use of empiric antibiotics is very important in infected neonates and the success of this practice is mainly reliant on the availability of an up-to-date antibiogram for currently used antibiotic drugs. In this study, we aim to determine the bacteriological profile and antibiotic susceptibility pattern of bacteria isolated from blood or/and urine cultures belonging to patients at the NICU. A total of 54 urine samples were collected in the period between January 2015 and December 2019. Data of infants with positive urine and blood bacterial isolates were gathered retrospectively. The most commonly isolated bacteria from urine observed were K. pneumoniae (44%) and E. coli (39%), while Acinetobacter baumannii (33%) and K. pneumoniae (22%) predominated in neonatal blood samples. The majority of uropathogens and blood isolates exhibited low resistance to imipenem and tigecycline, respectively. These antibiotics would be recommended for future use as empirical treatment in neonates with urinary tract infections and/or sepsis. This investigation highlights the importance of surveillance studies to manage and ensure the effectiveness of treatment plan for critically ill infants.